The cardiac phospho-proteome during pressure overload in mice: data descriptor - Wardman, Rhys; Grein, Steve; Schwartz, Jennifer; Stein, Frank; Heineke, Jörg (Scientific data, 2025)
Transaortic constriction (TAC) is a murine model of pressure overload-induced cardiac hypertrophy and heart failure. Despite its high prevalence during aortic stenosis or chronic arterial hypertension, the global alterations in cardiac phospho-proteome dynamics following TAC remain incompletely characterised. We present a database of the phospho-proteomic signature one day and seven days after TAC. Utilising proteomic and phospho-proteomic analyses, we quantified thousands of proteins and phosphorylation sites, revealing hundreds of differential phosphorylation events significantly altered in the cardiac response to pressure overload. Our analysis highlights significant changes in hypertrophic signalling, metabolic remodelling, contractile function, and the stress response pathways. We present proteomic data from the main cardiac cell types (endothelial cells, fibroblasts and cardiomyocytes) to reveal the cellular localisation of the detected phospho-proteins, offering insights into temporal and site-specific phosphorylation events, facilitating the potential discovery of novel therapeutic targets and biomarkers. By making this resource publicly available (ProteomeXchange with identifier PXD061784) we aim to enable further exploration of the molecular basis of cardiac remodelling and advance translational research in heart failure.
Gesehen am 04.11.2025